Assessing the effectiveness of modern dressing and Hamizal Bridge Offloading (HBO) among diabetic mellitus patients with plantar wound - Hamizal, Hamid (2022)
Diabetes Mellitus (DM) is a major public health concern in Malaysia, and the prevalence of Type 2 diabetes is 18.3% in 2019. According to the International Diabetic Federation 2019, 463 million people have diabetes, and this number is projected to reach 578 million by 2030 and 700 million by 2045. Diabetes Foot Ulcers (DFU) are the major complication among DM patients. In 2011, modern wound dressing has been used to treat DFU in Malaysia. However, it is not widely practiced in hospitals and health clinics. The objective of this study is to assess the effectiveness of modern dressing and Hamizal Bridge Offloading (HBO) in treating plantar wounds among DM patients. This qualitative study was adopted using a descriptive design and, individual interviews were conducted face-to-face with six respondents who have diabetic wounds on the soles of their feet. The collection of the data was conducted through voice recording at Centre of Excellence Wound Care, Senawang Health Clinic, Negeri Sembilan. The findings from this study are consistent with the findings of several studies related to modern dressing and Hamizal Bridge Offloading (HBO) among Diabetic Mellitus patients with a plantar wound. In addition, the findings of the data obtained show a patient’s wound healing within a month after using HBO and modern dressing. Modern Dressing with HBO treatment is very effective in assisting to help wound healing and reducing the amputation rate on a patient's limbs. Moreover, it can reduce the cost of treatment in terms of purchasing offloading products on the market.